2011
DOI: 10.1016/j.jpsychires.2010.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Psychometrics of a brief measure of anxiety to detect severity and impairment: The overall anxiety severity and impairment scale (OASIS)

Abstract: Brief measures of anxiety related severity and impairment that can be used across anxiety disorders and with subsyndromal anxiety are lacking. The Overall Anxiety Severity and Impairment Scale (OASIS) have shown strong psychometric properties with college students and primary care patients. This study examines sensitivity, specificity, and efficiency of an abbreviated version of the OASIS that takes only 2-3 minutes to complete using a non-clinical (college student) sample. 48 participants completed the OASIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
89
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 28 publications
10
89
2
2
Order By: Relevance
“…As in prior studies, the OASIS demonstrated strong psychometric properties, including adequate internal consistency and convergent validity with other measures of emotional distress. Similar to prior studies (Campbell-Sills et al, 2009;Norman et al, 2011), we found support for a unitary factor structure of the OASIS with adequate model fit only when error variance indices of the first two items were allowed to correlate. This result is unsurprising given that these two items are logically contingent on each other; i.e., if anxiety symptoms have not occurred (a frequency rating of 0), severity must also be zero.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…As in prior studies, the OASIS demonstrated strong psychometric properties, including adequate internal consistency and convergent validity with other measures of emotional distress. Similar to prior studies (Campbell-Sills et al, 2009;Norman et al, 2011), we found support for a unitary factor structure of the OASIS with adequate model fit only when error variance indices of the first two items were allowed to correlate. This result is unsurprising given that these two items are logically contingent on each other; i.e., if anxiety symptoms have not occurred (a frequency rating of 0), severity must also be zero.…”
Section: Discussionsupporting
confidence: 83%
“…In the initial validation study, Norman and colleagues (2006) found that the OASIS possessed a unitary factor structure and satisfactory test-retest reliability, convergent validity, and divergent validity in a sample of college students. Two subsequent studies examined the properties of the OASIS in primary care patients who were referred to a treatment study for anxiety disorders (Campbell-Sills et al, 2009) and college students (Norman et al, 2011). Consistent with the initial study, both studies found adequate psychometric properties and support for a unitary factor structure; however, the authors further refined the singlefactor model by allowing the error terms of the first two items to be freely estimated.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations